Development and application of a highly selective biomimetic sensor for detection of captopril, an important ally in hypertension control - Wong, Ademar [UNESP]; Lanza, Marcos R. V.; Sotomayor, Maria Del Pilar Taboada [UNESP] (Bentham Science Publishers, 2010)
A biomimetic sensor is proposed as a promising new analytical method for determination of captopril in different classes of samples. The sensor was prepared by modifying a carbon paste electrode with iron (II) phthalocyanine bis(pyridine) [FePc(dipy)] complex. Amperometric measurements in a batch analytical mode were first carried out in order to optimize the sensor response. An applied potential lower than 0.2 V vs Ag|AgCl in 0.1 mol L -1 of TRIS buffer at pH 8.0 provided the best response, with a linear range of 2.5 x 10 -5 to 1.7 x 10 -4 mol L -1. A detailed investigation of the selectivity of the sensor, employing seventeen other drugs, was also performed. Recovery studies were carried out using biological and environment samples in order to evaluate the sensor's potential for use with these sample classes. Finally, the performance of the biomimetic sensor was optimized in a flow injection (FIA) system using a wall jet electrochemical cell. Under optimized flow conditions, a broad linear response range, from 5.0 x 10 -4 to 2.5 x 10 -2 mol L -1, was obtained for captopril, with a sensitivity of 210 ± 1 μA L mol -1. © 2010 Bentham Science Publishers Ltd.
Keywords: Biomimetic sensor; Captopril; FIA analysis; Iron phthalocyanine; amitriptyline; captopril; captopril plus hydrochlorothiazide; carbon; clindamycin; diclofenac; digoxin; dipyrone; ephedrine; ferrous ion; fluconazole; iron complex; lidocaine; mebendazole; metronidazole; neomycin; paracetamol; phthalocyanine; pyridine; pyridoxine; quinine; ranitidine; secnidazole; tetracycline; trometamol; amperometric biosensor; analytic method; biomimetics; complex formation; electrochemical analysis; electrode; flow injection analysis; hypertension; priority journal; sensitivity and specificity; sensor; Adult; Antihypertensive Agents; Biosensing Techniques; Carbon; Electrochemistry; Electrodes; Ferrous Compounds; Humans; Hypertension; Molecular Structure; Sensitivity and Specificity; Water Pollutants, Chemical; Young Adult